A semi empirical kinetic approach to study nanoparticle catalysis for piperidinolysis of ionized phenyl salicylate in the presence of inert salts / Muhammad Azri Mohd Noh - Muhammad Azri , Mohd Noh (2017)
The present study is focused on the effect of the TTABr/MX/H2O-nanoparticles on the rate of piperidinolysis of ionized phenyl salicylate where TTABr represents tetradecyltrimethylammonium bromide and MX = NaCl, NaBr and CnH2n+1CO2Na with n = 4, 5, 6 and 7, and sodium salts of halobenzoic acids. Pseudo-first-order rate constant (kobs) for the piperidinolysis of ionized phenyl salicylate at 35°C and constant concentration of [PSa-]T = 0.2 mM, [Pip]T = 0.1 M, [NaOH] = 30 mM, [TTABr]T and different [MX] follow an empirical relationship which gives two empirical constants, Xkcat and KX/S. The removal of PSa- from bulk aqueous phase to the pseudo micellar phase by counterion X through ion exchange process X-/PSa- are responsible for the monotonic increase in kobs when the concentrations of MX were increased. The value of ion exchange constant/relative counterion (X) binding constant, RXBr were calculated from the relationship; RXBr = Xkcat/Brkcat. The values of RXBr for X = C4H9CO2-, C5H11CO2-, C6H13CO2-, and C7H15CO2- are increasing with increase in the number of alkyl chain of counterion X. Larger values of KXBror RXBr was observed for X = 4-halobenzoate ions than that for X = 2-halobenzoate ions due to isomeric factors. The values of KXBror RXBr for X = 2- and 4-halobenzoate ions determined in the presence of TTABr were compared with previously determined KXBror RXBr values in the presence of cetyltrimethylammonium bromide (CTABr). Steady shear rheological measurements were carried out on TTABr/MX/H2O nanoparticles system at [TTABr]T = 15 mM for MX = C7H15CO2Na, 2-FBzNa, 4-FBzNa, 2-ClBzNa, 4-ClBzNa, 2-BrBzNa, 4-BrBzNa, 2-IBzNa and 4-IBzNa. Newtonian fluid behavior was shown by TTABr/MX/H2O systems for MX = C7H15CO2Na, 2-FBzNa, 4-FBzNa, 2-ClBzNa, 2-BrBzNa and 2-IBzNa. The plots of zero shear viscosity (η0) vs. [MX] at 35°C and 15 mM TTABr shows the presence of viscosity maximum for MX = 4-ClBzNa, 4-BrBzNa and 4-IBzNa which indicates the presence of wormlike micelles in the micellar systems. Plots of η0 vs. [MX] of TTABr/MX/H2O systems at different temperature ranges from 20 to 55°C show nonlinear and linear Arrhenius behavior for MX = 2-FBzNa, 4-FBzNa and 4-ClBzNa, 4-BrBzNa, 4-IBzNa, respectively. The value of KXBror RXBr were found to correlate with the rheological results obtained in the present study.